Export Mix Changes and Firm Performance: Evidence from Chile - Roberto Álvarez Espinoza; Andrés Zahler (Inter-American Development Bank (IDB), 2014)
In this paper we analyze changes in the export mix of Chilean firms, looking particularly at differences between large firms and SMEs. To do that, we use detailed information of exported products by firms during the period 1995-2005. Our econometric results, which look at the impact of export product churning on firm performance, are heterogeneous by type of change in export mix and by firm size. In general, export mix changes are associated with improvements on productivity, although our results suggest that this positive effect is only for SMEs. In terms of employment and sales, we find that export product churning has positive effect on large firms and lower - and in some case negative - on SMEs. It seems that changes in export mix are more important for firm growth in large firms, but not in terms of productivity. In contrast, SMEs can have a higher potential for productivity improvement through export product churning but this does not translate necessarily in significant increase in sales and employment.
hdl:11319/6514
Keywords: D22; F14; L25; 330; Productivity; Firms Growth; Export Mix; International Trade; SMEs; Large Firms